2016
DOI: 10.1371/journal.pone.0150835
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Promoter Single Nucleotide Polymorphisms Are Associated with Clinical Disease Severity

Abstract: The large majority of human immunodeficiency virus type 1 (HIV-1) markers of disease progression/severity previously identified have been associated with alterations in host genetic and immune responses, with few studies focused on viral genetic markers correlate with changes in disease severity. This study presents a cross-sectional/longitudinal study of HIV-1 single nucleotide polymorphisms (SNPs) contained within the viral promoter or long terminal repeat (LTR) in patients within the Drexel Medicine CNS AID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…Recent studies have shown the patient-derived HIV-1 sequences displayed a measureable and substantial amount of genetic variation even on stable, uninterrupted HAART with region-specific as well as patient-specific mutation rates, indicating that certain regions may be more easily targeted than others 2 , 32 35 . As is demonstrated in the cross-sectional data analysis performed herein, the same difficulty with target variation will be encountered within a patient.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown the patient-derived HIV-1 sequences displayed a measureable and substantial amount of genetic variation even on stable, uninterrupted HAART with region-specific as well as patient-specific mutation rates, indicating that certain regions may be more easily targeted than others 2 , 32 35 . As is demonstrated in the cross-sectional data analysis performed herein, the same difficulty with target variation will be encountered within a patient.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is evidence of single nucleotide polymorphisms in transcription factor binding sites within the LTRs of different HIV-1 subtypes [18–21]. This sequence variation leads to subtype-specific differences in proviral gene expression, thereby imparting unique biological characteristics to a given strain.…”
Section: Antisense Transcription Among Exogenous Retrovirusesmentioning
confidence: 99%
“…Neuropsychological assessments of HIV-1-infected patients currently enrolled in the CARES Cohort at the Drexel University College of Medicine (Aiamkitsumrit et al , 2014; Dampier et al , 2016; Li et al , 2011; Nonnemacher et al , 2016; Parikh et al , 2014; Shah et al , 2014) revealed a range of neurocognitive function, as indicated by GDS. Most Cohort patients for which Vpr sequences were available had GDS ≤2 (Fig.…”
Section: Resultsmentioning
confidence: 99%